(untitled) (Darya Ganj, New Delhi, 2001)
Contents of material: Multimedia library. Cataloguing technologies. Managing the catalogue deparment. Multimedia resources. Oline services. Miltimedia medium. Multimedia catalogue and the computer. Online technical support systems
Keywords: Library science,Cataloging,Multimedia library services